Developing repayment risk management model of Qarḍ al-Ḥasan financing for SMEs in Islamic banks - Al-Melahi, Abdellah Ali Ahmed; Adam Sa'ad, Auwal; Syed Jaafar Alhabshi, Syed Musa (Springer, Cham, 2022)
This study focuses on repayment risk associated with Qarḍ al-Ḥasan financing in Islamic banks. The study aims to review repayment risk management of Qarḍ al-Ḥasan for SMEs Financing, which is proposed to be utilized for SMEs financing needs. The study initiated a model on how the Islamic banks can manage repayment risk and get sources for default Qarḍ al-Ḥasan. The proposed initiative suggests the use of Set-Aside Earning, Zakāt and Qarḍ al-Ḥasan Takaful for default Qarḍ al-Ḥasan. The Shariah model used for this initiative is Qarḍ al-Ḥasan financing model. The study follows series of approaches to achieve its objectives. A descriptive method was used to study the subject matter. The study also uses the comparative analytical approach to analyze and compare the annual financial reports issued by some Islamic banks. The study finds that Islamic banks possessed a perfect opportunity to manage repayment risk of Qarḍ al-Ḥasan financing SMEs by channeling the Set-Aside Earnings and Zakāt for default Qarḍ al-Ḥasan. The ReRMQAF model can be applicable for repayment risk to SMEs financing using Qarḍ al-Ḥasan default sources which that Set-Aside Earnings, part of Zakāt and Qarḍ al-Ḥasan Takaful. The study concludes with a few recommendations, including that the Islamic banks should offer their Set-Aside Earnings, part of Zakāt and Qarḍ al-Ḥasan Takaful for defaulted Qarḍ al-Ḥasan funds. The study also proposes that the Islamic banks can search for other sources such as waqf and crowdfunding to reduce the repayment risk of Qarḍ al-Ḥasan default to SMEs financing. The study has also recommended a particular supervisory policy and regulations that would guide and support the proposed model, which is named Repayment Risk Management of Qarḍ al-Ḥasan Financing (ReRMQAF).